2009
DOI: 10.1007/s00122-009-1222-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validation of quantitative trait loci for spikelets per panicle and 1,000-grain weight in rice (Oryza sativa L.)

Abstract: This study identified four and five quantitative trait loci (QTLs) for 1,000-grain weight (TGW) and spikelets per panicle (SPP), respectively, using rice recombinant inbred lines. QTLs for the two traits (SPP3a and TGW3a, TGW3b and SPP3b) were simultaneously identified in the two intervals between RM3400 and RM3646 and RM3436 and RM5995 on chromosome 3. To validate QTLs in the interval between RM3436 and RM5995, a BC(3)F(2) population was obtained, in which TGW3b and SPP3b were simultaneously mapped to a 2.6-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 34 publications
2
45
0
4
Order By: Relevance
“…The PZM and PMT populations and their planting methods have been described by Xing et al (2002) and Liu et al (2010). The PZT population used in this study consists of 190 F 7 RILs derived from a singleseed descendent of the cross between Zhenshan 97 and Teqing.…”
Section: Experimental Populations and Phenotypic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PZM and PMT populations and their planting methods have been described by Xing et al (2002) and Liu et al (2010). The PZT population used in this study consists of 190 F 7 RILs derived from a singleseed descendent of the cross between Zhenshan 97 and Teqing.…”
Section: Experimental Populations and Phenotypic Measurementsmentioning
confidence: 99%
“…QTL analysis for SPP and TGW was conducted in PZT and for SPP in PZM. The objectives of combining the QTL results of the PZT population with those of SPP and TGW in the PZM and PMT population Liu et al 2010) were to (1) uncover how many QTLs for SPP and TGW could be detected in the three populations, (2) evaluate the relationship of QTL additive effects detected in different populations, and (3) determine the most beneficial alleles from these three varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Perera et al (1986) suggested that genes with additive, dominant, and epistatic effects controlled both the number of tillers at maturity and the number of panicles per plant. According to Padmaja et al (2008) and Liu et al (2010), there is a predominance of additive gene action for number spikelet per panicle. However, Panwar and Paroda (1983) showed that grain yield is controlled by both additive and dominant gene effects.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al(2006) identified QTLs between RM544 and RM310 on chromosome 8 for heading date, plant height and panicle size co-segregating in trait-performance derived near-isogenic lines of rice. Recently, Liu et al(2009) also identified a QTL for SPP between RM126 and RM483 within the region of chromosome 8. However, due to insufficient molecular markers and small segregation populations, the precise location of the QTLs is still unknown.…”
Section: Discussionmentioning
confidence: 95%